A Holistic Approach to School Health: Implementation and Challenges in Secondary Education - Muhammad Ibrohim; Riyuzen Praja Tuala; Ilhami (Journal of Educational Management Research, 2026)
Effective implementation of the School Health Effort Program (UKS) is essential for promoting students’ health and fostering a healthy school environment. The purpose of this research is to examine the implementation of the School/Madrasah Health Effort Program through health education, health services, and the development of a healthy school environment. A qualitative descriptive approach was employed in this study. Data were collected through observation, interviews, and documentation involving key informants such as the principal, UKS teachers, and students. The collected data were analyzed through the processes of data reduction, data display, and conclusion drawing. The findings indicate that the UKS program has been implemented through three main components. Health education is conducted through health counseling and the cultivation of clean and healthy lifestyle habits among students. Health services are provided through the utilization of the school health unit room and collaboration with local health institutions. In addition, the development of a healthy school environment is supported through classroom cleaning duties and routine school cleanliness activities. These findings imply that strengthening collaboration among school stakeholders and continuous health education can enhance the effectiveness and sustainability of school health programs.